Avaliação normativa das salas de vacinas na rede pública de Saúde do municipio de Marilia, Estado de São Paulo, Brasil 2008 -2009. - Kelly Cristina Encide de Vasconcelos; Rocha, Suelen Alves [UNESP]; Ayres, Jairo Aparecido [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: to evaluate the standardization of vaccination rooms in the Municipality of Marília, State of São Paulo, Brazil. Methods: descriptive and exploratory study, realized in 2008-2009; the instrument used was the Supervision in Vaccination Rooms, of the Ministry of Health; variables analyzed were general aspects of the vaccination room, technical procedures, cold chain, information system, post-vaccination adverse events, special immunobiologicals, epidemiological surveillance and health education; the score achieved classifies the room (90.0-100.0% = ideal; 76.0-89.0% = good; 50.0-75.0% = fair; <50.0% = insufficient); overall index for each point was calculated as the average score of all rooms. Results: technical procedures, information system, post-vaccination adverse events and special immunobiologicals were scored as ideal; cold chain, epidemiological surveillance and health education were scored as good; and to general aspects of the vaccination room, the evaluation was fair. Conclusion: general index for vaccination rooms in the municipality was considered ideal.

Objetivo: avaliar a padronização das salas de vacinas do Município de Marília, Estado de São Paulo, Brasil. Métodos: estudo descritivo exploratório, realizado em 2008-2009; utilizou-se o instrumento de Supervisão em Sala de Vacinação do Ministério da Saúde; como variáveis, foram estudados os aspectos gerais da sala de vacinação, procedimentos técnicos, rede de frio, sistema de informações, eventos adversos pós-vacinação, imunobiológicos especiais, vigilância epidemiológica e educação em saúde; a pontuação alcançada classificou a sala (90,0-100,0% = ideal; 76,0-89,0% = bom; 50,0-75,0% = regular; <50,0% = insuficiente); o índice geral para cada aspecto foi calculado como a média da pontuação de todas as salas. Resultados: procedimentos técnicos, sistema de informações, eventos adversos pós-vacinação e imunobiológicos especiais receberam o conceito ideal; rede de frio, vigilância epidemiológica e educação em saúde receberam o conceito bom; e aos aspectos gerais da sala de vacinação, atribuiu-se o conceito regular. Conclusão: o índice geral das salas de vacinas do município foi considerado ideal.
Evaluation of vaccination rooms in the primary health care network of the Municipality of Marília, State of São Paulo, Brazil, 2008-2009
Keywords: Immunization; Immunization programs; Health care services evaluation; Imunização; Programas de imunização; Avaliação de serviços de saúde